SYSTEM ON CV SALARY ADMINISTRATION. ZAM ZAM TRIO USING MICROSOFT VISUAL BASIC 6.0 - Suryo Nugroho; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Scientific research is aimed to make the salary administration system in CV. Trio Zam - Zam. ranging from data input to the preparation of reports using Microsoft Visual Basic 6.0. It is scientific research which is the study by collecting data - data. The author obtained these data by conducting interviews related to the employees at the company. From this research we can conclude that by using computerized will gain the ease and speed up the process of calculating employees' salaries as well as making monthly reports.